Cryptococcus neoformans Csn1201 Is Associated With Pulmonary Immune Responses and Disseminated Infection - Yang, Ya-li; Fan, Yi-bin; Gao, Lei; Zhang, Chao; Gu, Ju-lin; Pan, Wei-hua; Fang, Wei (Frontiers in Immunology, 2022)
Cryptococcus neoformans is a major aetiological agent of fungal meningoencephalitis. The outcome of cryptococcosis depends on the complex interactions between the pathogenic fungus and host immunity. The understanding of how C. neoformans manipulates the host immune response through its pathogenic factors remains incomplete. In this study, we defined the roles of a previously uncharacterised protein, Csn1201, in cryptococcal fitness and host immunity. Use of both inhalational and intravenous mouse models demonstrated that the CSN1201 deletion significantly blocked the pulmonary infection and extrapulmonary dissemination of C. neoformans. The in vivo hypovirulent phenotype of the csn1201Δ mutant was attributed to a combination of multiple factors, including preferential dendritic cell accumulation, enhanced Th1 and Th17 immune responses, decreased intracellular survival inside macrophages, and attenuated blood–brain barrier transcytosis rather than exclusively to pathogenic fitness. The csn1201Δ mutant exhibited decreased tolerance to various stressors in vitro, along with reduced capsule production and enhanced cell wall thickness under host-relevant conditions, indicating that the CSN1201 deletion might promote the exposure of cell wall components and thus induce a protective immune response. Taken together, our results strongly support the importance of cryptococcal Csn1201 in pulmonary immune responses and disseminated infection.